The interplay between the anticipation and subsequent online processing of emotional stimuli as measured by pupillary dilatation: the role of cognitive reappraisal - Vanderhasselt, Marie-Anne; Remue, Jonathan; Ng, Kwun Kei; De Raedt, Rudi (Frontiers in Psychology, 2014)
Emotions can occur during an emotion-eliciting event, but they can also arise when anticipating the event. We used pupillary responses, as a measure of effortful cognitive processing, to test whether the anticipation of an emotional stimulus (positive and negative) influences the subsequent online processing of that emotional stimulus. Moreover, we tested whether individual differences in the habitual use of emotion regulation strategies are associated with pupillary responses during the anticipation and/or online processing of this emotional stimulus. Our results show that, both for positive and negative stimuli, pupillary diameter during the anticipation of emotion-eliciting events is inversely and strongly correlated to pupillary responses during the emotional image presentation. The variance in this temporal interplay between anticipation and online processing was related to individual differences in emotion regulation. Specifically, the results show that high reappraisal scores are related to larger pupil diameter during the anticipation which is related to smaller pupillary responses during the online processing of emotion-eliciting events. The habitual use of expressive suppression was not associated to pupillary responses in the anticipation and subsequent online processing of emotional stimuli. Taken together, the current data suggest (most strongly for individuals scoring high on the habitual use of reappraisal) that larger pupillary responses during the anticipation of an emotional stimulus are indicative of a sustained attentional set activation to prepare for an upcoming emotional stimulus, which subsequently directs a reduced need to cognitively process that emotional event. Hence, because the habitual use of reappraisal is known to have a positive influence on emotional well-being, the interplay between anticipation and online processing of emotional stimuli might be a significant marker of this well-being.